Policy to regional linkage connecting science and technology with industrial production in Japan and policy implications for Vietnam - Dung, Bui Tien; Tung, Huynh Van; Khiem, Vu Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
This article outlines the policy initiatives of the Japanese government through periods to link in between science - technology and the regional industrial production. The policy initiatives of the Japanese government following this direction are implemented by focusing on enhancing the links among technical-engineering universities and manufacturing firms in regional innovation systems. The regional linkage model connecting the commodity production chain based on new scientific and technological knowledge, overcomes the socio-economic gap in industrialized areas compared to the underdeveloped ones. From experiences on Japan, there are some meanings and values that Vietnam can refer to. Code: 18120501